English L2 reading getting to the bottom - Birch, Barbara M. (ESL and Applied Linguistics Professional Series., 2007)
English L2 Reading: Getting to the Bottom, Second Edition remains a comprehensive, myth-debunking examination of how L1 features (orthographic system, phonology, morphology) can influence English L2 reading at the "bottom" of the reading process. It provides a thorough but very accessible linguistic/psycholinguistic examination of the lowest levels of the reading process. It is both theoretical and practical. The goal is to balance or supplement (not replace) top-down approaches and methodologies with effective low-level options for teaching English reading. Core linguistic and psycholinguistic concepts are presented within the context of their application to teaching.